Financial Knowledge And Financial Behavior Among Educati onal Staff (A Survey on Educational Staff in Universitas Kuningan) - Herma Wiharno; Dadang Suhendar; Munir Nur Komarudin (Jurnal Akuntansi dan Pajak, 2021)
Abtract This study aims to investigate the effect of demographic characteristics on financial knowledge and financial behavior as well as the effect of financial knowledge on financial behavior. The method applied in this study was descriptive and verification method. This study was conducted in Universitas Kuningan with educational staff as the unit of analysis. By applying Stratified Cluster Proportional Random Sampling, 105 educational staff was selected as the sample of this study. The results of descriptive analysis revealed that based on age group, education level, and income level, educational staff with age of >45 years old, education level of S-2, and income level of >Rp. 3 million has a higher level of financial knowledge and financial behavior compared to other educational staff. Meanwhile, the results of verification analysis indicated that education level and income level have a significant effect on financial knowledge and financial behavior, and financial knowledge has a positive effect on financial behavior. Keywords: demographic characteristics, financial knowledge, financial behavior.